If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + 9) = -21 + 19 Reorder the terms: 2(9 + 5x) = -21 + 19 (9 * 2 + 5x * 2) = -21 + 19 (18 + 10x) = -21 + 19 Combine like terms: -21 + 19 = -2 18 + 10x = -2 Solving 18 + 10x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 10x = -2 + -18 Combine like terms: 18 + -18 = 0 0 + 10x = -2 + -18 10x = -2 + -18 Combine like terms: -2 + -18 = -20 10x = -20 Divide each side by '10'. x = -2 Simplifying x = -2
| z-7z=6z-8-z | | 10w-13w=-6 | | 4g-7+5g-5=3(-4+3G) | | 9x+9=3+45 | | -9+3b+4-b= | | 9y=8(y+17) | | 8-6x-5-6x=6 | | 5x+9y=8 | | 3x+22=x+18 | | 4-.5q=33-q | | 5z-18-z+2=0 | | 20(14.10)=25x+7 | | -6(x+7)-44=4-36 | | 14=5x-2 | | 6x+(5x-6)= | | 4(6-t)=-2(3+t) | | -2v+4=-6(v+6) | | y+3=-0.3333(x-7) | | 6.4r=-9.6 | | -3=5+t | | 3t+4t=0 | | 7x-(9x-15)=14-(x+19) | | 9x+4-x=7+7x+2 | | T=4+3.34 | | D(a+b)=g | | -38=19y | | 3z-7=23 | | 4-2m=7-3m | | -24+x=8x | | 8x+10=-6 | | -2(p+6)-2(5p+7)= | | 4a+8=8 |